Factors contributed towards the development of Small and Medium Enterprises (SMEs) in Tanjung Malim / Siti Noraini Haji Mujari (Faculty of Business and Management, 2008)
The purpose of the present study is to examine the five factors that contributed to the development of Small and Medium Enterprise (SMEs) in Tanjung Malim which are strengthening enabling infrastructure, building the capacity and capability of SMEs, enhancing access to financing, increasing market access and enhancing growth and competitiveness. Therefore, the proposal research framework was developed with the intention of examining this relationship. In this study, descriptive research was conducted to obtain the information needed. It involved acquiring primary data, preparing questionnaires, sampling method and deciding on how variables will be measured and analyzed. This study was conducted at Tanjung Malim. After conducted this study, the result revealed that where five strategic thrusts have significant relationship with development of Small and Medium Enterprise (SMEs) in Tanjung Malim. The researcher has come out with several recommendations that SMEs in Tanjung Malim can use for future plan, manage their business operations and to achieve sustainable economic growth not only for Perak's but for country's economy.